Adenomas of the large intestine after cholecystectomy. Issue 8 (August 1984) - Mannes, A G; Weinzierl, M; Stellaard, F; Thieme, C; Wiebecke, B; Paumgartner, G
Abstract : The frequency of adenomas of the large intestine in 331 cholecystectomised patients who underwent total colonoscopy was compared with that of a control group of patients with asymptomatic cholelithiasis who were matched for age and sex. Whereas no significant difference in the frequency of adenomas was found between two groups, a subgroup of patients aged 60-80 years with a postcholecystectomy interval of 10 years or greater exhibited a significantly (p less than 0.05) greater frequency of adenomas (38.5%) than matched patients with a postcholecystectomy interval of less than 10 years (21.8%) and matched controls with cholelithiasis (23.7%). This increase in the frequency of adenomas was primarily accounted for by an increase in the percentage of tubular adenomas (p less than 0.05) and corresponded to an increase in the frequency of cancer (p less than 0.05) of the large bowel.